Legal Protection of Debtors for Fiduciary Collateral Objects Whose Debts Have Been Paid Off Based on the Fiduciary Guarantee Law and Government Regulation Number 21 of 2015 - Wennie Melannie; Faisal Santiago (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Fiduciary Guarantee is an accessory agreement that follows the principal agreement it guarantees. If the principal agreement ends, the Fiduciary Guarantee agreement also ends. However, the recording of the encumbrance and granting of the Fiduciary Guarantee contained in the Fiduciary Guarantee Register Book at the Fiduciary Registration Office can be crossed out or deleted (roya) if requested by the Fiduciary Beneficiary (Article 25 paragraph (3) of Law No. 42/1999 on Fiduciary Guarantee). Legal protection is provided in the event of full repayment or repayment of the debt secured by the Fiduciary Guarantee Object. Based on Article 25 paragraph (1) of Law No. 42/1999, this is one of the reasons for fiduciary abolition. The Fiduciary is obliged to notify the abolition of the Fiduciary Guarantee to the Fiduciary Registration Office so that the Fiduciary Guarantee can be removed from the Fiduciary Guarantee Register Book. The nature of the Fiduciary Guarantee depends on the existence of the receivables whose repayment is guaranteed. If the receivables are written off due to debt repayment or disposal, the related Fiduciary Guarantee is automatically deleted. If the Creditor does not perform the deletion, the Debtor may take legal action, either through litigation or non-litigation. An obstacle to legal protection for the Fiduciary is if the Fiduciary does not complete the Fiduciary Guarantee Certificate online. Law No. 42/1999 and its implementing regulation, PP No. 21/2015, do not include sanctions for the Fiduciary or its representative if the Fiduciary Guarantee Certificate is not done. This results in no legal certainty over the object of the Fiduciary Guarantee if the Fiduciary does not perform it, because the object used as collateral remains registered with the Ministry of Law and Human Rights and the Fiduciary Guarantee Certificate is still considered valid and cannot be re-registered in accordance with Article 17 paragraph (2) of Government Regulation No. 21 of 2015.